A look behind the curtain: Measuring the complex economic effects of regional structural funds in Germany. Issue 2 (14th June 2018) - Eberle, Jonathan; Brenner, Thomas; Mitze, Timo
Abstract: This paper investigates the mutual impact channels of Germany's major regional policy instrument (GRW) on regional economic development. Different from earlier studies which have predominately focused on a partial assessment of output effects, we explicitly endogenize the factor inputs of the underlying production function. This allows us to comprehensively assess the role of the GRW in driving per capita output, employment, human and physical capital intensities as well as the region's technological growth. The results from a spatial panel vector autoregressive model show that GRW funding has significant positive effects on regional output, the employment rate and human capital intensity.